Enforcing the Law Against Animal Cruelty Perpetrators: The Animal Husbandry and Veterinary Health Act - Setiawati, Dewi; Hidayat, Sarip; Akhmaddhian, Suwari; Budiman, Haris (Unifikasi : Jurnal Ilmu Hukum, 2024)
Violence extends beyond humans, with a troubling increase in cases of animal cruelty. The study aims to critically assess and analyse the enforcement of legal measures against animal cruelty perpetrators in accordance with Law No. 41 of 2014 on Animal Husbandry and Veterinary Health. The study employs a juridical-empirical approach, utilising a descriptive-analytical research design. The research reveals that individuals responsible for animal cruelty can be held accountable under Article 302 of the Indonesian Penal Code, Article 66A of Law No. 41 of 2014 on Animal Husbandry and Veterinary Health, and Government Regulation No. 95 of 2012 on Veterinary Health and Animal Welfare. However, the enforcement of these legal provisions remains suboptimal. It is primarily due to insufficient public awareness of animal welfare, resulting in underreporting of abuse cases, which in turn impedes the effectiveness of law enforcement agencies in addressing the issue. The conclusion reveals that the insufficient public awareness and legal consciousness regarding Law No. 41 of 2014 on Animal Husbandry and Veterinary Health, alongside the prohibition of animal cruelty, has allowed instances of abuse to occur without being reported or addressed, thereby exposing the inadequacy of current law enforcement. It is imperative to reconsider and strengthen the legal framework by imposing more severe criminal penalties on animal cruelty offenders. Moreover, establishing a specialised task force for animal welfare could provide a strategic breakthrough in combating these violations effectively.